Autophagic Cell Death During Development – Ancient and Mysterious - Schwartz, Lawrence M. (Frontiers in Cell and Developmental Biology, 2021)
While cell death is a normal and essential component of development and homeostasis, dysregulation of this process underlies most human diseases, including cancer, autoimmunity and neurodegeneration. The best characterized mechanism for cell death is apoptosis, although some cells die by a distinct process known as autophagy-dependent cell death (ADCD). Autophagy is mediated by the formation of double membrane vesicles that contain protein aggregates, damaged organelles like mitochondria, and bulk cytoplasm, which then fuse with lysosomes to degrade and recycle their contents. Autophagy is typically viewed as an adaptive process that allows cells to survive stresses like nutrient deprivation, although increasing evidence suggests that it may also mediate cell death during development and pathogenesis. An aggressive form of autophagy termed autosis has been described in cells following either ischemia/reperfusion injury or in response to autophagy-inducing proteins like Tat-Beclin 1. Despite an extensive literature on autophagic cell death in a variety of contexts, there are still fundamental gaps in our understanding of this process. As examples: Does autophagy directly kill cells and if so how? Is ADCD activated concurrently when cells are triggered to die via apoptosis? And is ADCD essentially a more protracted version of autosis or a pathway? The goal of this mini-review is to summarize the field and to identify some of the major gaps in our knowledge. Understanding the molecular mechanisms that mediate ADCD will not only provide new insights into development, they may facilitate the creation of better tools for both the diagnostics and treatment of disease.